Pengaruh Konflik Peran Ganda Dan Stres Kerja Terhadap Kinerja Pada Perawat Wanita Di RSUD Prof.DR.M.A Hanafiah, SM Batusangkar - Atika Suri; Rino Rino (Jurnal Salingka Nagari, 2023)
The purpose of this study is to see how multiple role conflict and work stress affect the performance of female nurses at Prof.Dr.M.A Hanafiah Hospital, SM Batusangkar. This type of study is causal. Nurses from Hanafiah Hospital Batusangkar participated in this study. Based on the slovin formula, the number of research samples was determined to be as many as 97 people, who were chosen using a purposive sampling technique. The data used in this study is primary data. Multiple regression is the analytical method used. In this study, data was analyzed using classical assumption analysis, multiple regression analysis, and hypothesis analysis. According to the findings of this study, 1) Multiple Role Conflict and Job Stress have a significant impact on performance. 2) Dual Role Conflict improves performance in a significant way. 3) Workplace stress improves performance in a significant way.